The Other in Everyman’s Body: Self and Exchange in Philip Roth’s Everyman - Moreira, Jéssica (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
Departing from Baudrillard’s account on economic exchange and symbols, the aim of the present paper is to demonstrate how Philip Roth’s Everyman can be interpreted in terms of exchange – cultural instead of economic – between mainstream culture and Jewish subculture and, simultaneously, how death and sex provide the sign values for these exchanges, characterising, in themselves, cultural tendencies. These exchanges will be interpreted mainly as trades between Self – or Same – and Other since, in the same way the Self defines itself through reference to what is Other, so these tendencies will be defined – or tried to be defined by the protagonist – as existing only insofar an Other opposes to it. This attempt can be read as a form of construction of a signification theory that is defined through differentiation and pervades the whole novel. The act of binary construction, nevertheless, results in failure as the Self finds itself unable to refer back to itself through the creation of “badges of difference” (Neill 8). This failure ultimately leads the protagonist to a disenchanted attitude, provoked by a sense of alienation towards his own body – supposed centre of selfhood. What I intend to prove by the end of the essay is that the plot of Everyman can be read as: 1. the story of a man trying to escape historicity and 2. ascribe meaning both outside and inside a psychological theory of Otherness and differentiation just to realise it is inescapable – as is stressed by the many instances in which circularity annuls meaning and imposes time’s indifference towards human affairs.